Dürer's lost masterpiece art and society at the dawn of a global world - Rublack, Ulinka 1967- (Oxford scholarship online, 2023)
This volume tracks the history of a turning point in the career of the celebrated German artist Albrecht Dürer (1471-1528), when he stopped painting altarpieces after arguing with a merchant patron over payment. As an eloquent homage to Dürer's life, it brings us closer to the creation and meaning of his paintings than ever before